Ethylene production from ethanol dehydration over non- modified and phosphorus modified zeolite Y - Soh, Jiah Chee (2017)
Ethylene is an important raw material for the downstream petrochemical industry. Significantly, with the shortage of natural resource and fossil fuel-derived energy, catalytic dehydration of ethanol to ethylene route has become compelling, and therefore has been drawing attention lately. In this work, commercial zeolite Y was screened to identify the best Si/Al ratio as well as analyze the catalysts’ physicochemical properties. Besides, zeolite Y and phosphorus modified zeolite Y were employed as catalysts to study the effect of reaction temperatures and ethanol partial pressure on dehydration of ethanol to form ethylene. Towards achieving this goal, zeolite Y with various Si/Al ratio (5.1:1. 12:1, 30:1, 60:1 and 80:1) were firstly screened; zeolite Y with Si/Al ratio 80:1, coded H-Y (80) demonstrated the best catalytic performance with high ethanol conversion and ethylene selectivity (73.0% and 99.5% respectively) at 773 K. Subsequently, wet impregnation technique was employed to modify the H-Y (80) with phosphoric acid solution. For activity evaluation, a bench-scale fixed-bed reactor was employed and only the gaseous product from ethanol dehydration was collected and subjected to GC analysis. From the results obtained, BET specific surface area of fresh catalysts showed decreasing trend with increasing phosphorus loadings. Moreover, phosphorus modification on H-Y (80) can decrease the volume of micropores and mesopores due to channel blocking by PO43-. In addition, the NH3-TPD analysis showed that the increase in phosphorus loading had increased the moderate-strong acid sites. Among all the phosphorus modified H-Y (80), 3.15P/H-Y (80) was shown to exhibit the highest ethanol dehydration activity, where the conversion of ethanol at 773 K was 66.45%. The ethylene selectivity over all the catalysts was almost similar, easily attaining values of greater than 88.0%. Based on the N2 physisorption and SEM-EDX analysis of spent catalysts, it can be confirmed that the there was less carbon deposition on phosphorus modified H-Y (80) and demonstrated a better stability during the reaction although this has come at the expense of reduced activity. In conclusion, H-Y (80) showed the best catalytic activity among all the tested zeolite Y, and phosphorus modification decreased the BET specific area but increase the strength of acid sites in the catalysts. From the results, high reaction temperature and low ethanol partial pressure favour ethanol dehydration by H-Y (80).